2017
DOI: 10.3141/2664-08
|View full text |Cite
|
Sign up to set email alerts
|

Carless or Car Later?: Declining Car Ownership of Millennial Households in the Puget Sound Region, Washington State

Abstract: Driving has been declining since the mid-2000s after six decades of constant growth, and millennials are allegedly leading the trend. This study investigates the decline of car mobility by using vehicle ownership data in the Puget Sound region of Washington State, where transit ridership is increasing faster than in most other large metropolitan areas. Poisson regression and simple simulation results show that millennial-specific impacts such as changing location and mobility preferences were associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Compared with the Baby Boomer generation, individuals in all other generations display a lower propensity of vehicle ownership and a higher propensity of transit use (except for the Silent Generation). These findings are along expected lines and consistent with recent evidence that younger cohorts are depicting lower levels of auto ownership and higher levels of transit use compared with prior generations ( 2022 ). In addition to these direct generational effects, this study also examined possible variations across generations in the effects of the childhood experience variables (through interactions of the childhood experience variables with the generational variables).…”
Section: Resultssupporting
confidence: 90%
“…Compared with the Baby Boomer generation, individuals in all other generations display a lower propensity of vehicle ownership and a higher propensity of transit use (except for the Silent Generation). These findings are along expected lines and consistent with recent evidence that younger cohorts are depicting lower levels of auto ownership and higher levels of transit use compared with prior generations ( 2022 ). In addition to these direct generational effects, this study also examined possible variations across generations in the effects of the childhood experience variables (through interactions of the childhood experience variables with the generational variables).…”
Section: Resultssupporting
confidence: 90%
“…As noted by Docherty and Marsden [4], contemporary imaginings of mobility are, to a large extent, crafted by the producers of mobility innovations. This happens because the automotive industry has high stakes in the development and positive marketing of AVs: The car is losing its original appeal and economic profitability, as younger generations seem to be consistently reducing its use [97,98]. The success of AVs would potentially mean a new prosperous phase for this industry [90].…”
Section: Application To Automated Transportmentioning
confidence: 99%
“…This can be explained by underrepresentation of the younger generations in our subsample as we focus on workers who drive their own cars. Recent travel behavior studies revealed that the younger generation (e.g., millennials) may drive less or not own cars (e.g., [44,45]). Therefore, it is likely that the younger generation may be underrepresented in our subsample.…”
Section: Study Area and Datamentioning
confidence: 99%